Problematika Pernikahan Anak Yang Bernasab Pada Ibu (Studi Kasus Di Kecamatan Grujugan Bondowoso) - Muhammad Juhariyanto; Laila Afifah (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
Abstract: Marriage is a very strong bond or mitsaqan ghalidzan, marriage not only justifies the relationship between husband and wife, more than that, one of the lessons of marriage is the maintenance of the lineage. In marriage, having a guardian for the bride and groom is one of the pillars of marriage. Where in a marriage a guardian is taken from the father's side and is called a nasab guardian, it is the nasab guardian who has the right to be the guardian in the implementation of the marriage. A girl who is only registered as her mother's daughter, she has no blood relationship with her biological father. Directly, the child does not have a lineage guardian, because the lineage guardian is taken from the father's lineage, so the marriage registrar refuses to marry him off, because he does not have a mujbir guardian. Based on this problem, the author is interested in researching how marriages are resolved for women who are only related to their mother and who do not have a direct line to their biological father and what faktors cause them to be registered as the mother's child. In the research that will be carried out, the author chose a location in Grujugan District, Bondowoso Regency. This research is a type of field research using qualitative methods. The results of this research are the implementation of child marriages that are related to their mother only, so the marriage uses a guardian judge instead of the guardian of the lineage, with a decision from the Religious Court in determining the guardian judge. Meanwhile, the cause of being recorded as only the mother's child in Grujugan District is due to two faktors, namely, children who were produced outside of marriage, and whose whereabouts are unknown. Keywords: Marrriage, Lineagge, Grujugan Bondowoso. Abstrak: Pernikahan merupakan ikatan yang sangat kuat atau mitsaqan ghalidzan, pernikahan bukan hanya menghalalkan hubungan suami istri lebih dari itu hikmah perkawinan salah satunya yakni terpeliharanya nasab. Dalam pernikahan adanya seorang wali dari mempelai wanita merupakan salah satu dari rukun nikah. Yang mana dalam pernikahan seorang wali itu diambil dari pihak ayah dan disebut dengan wali nasab, wali nasablah yang berhak menjadi wali dalam pelaksanaan pernikahan. Seorang anak perempuan yang hanya tercatat sebagai anak ibu saja, ia tidak memiliki hubungan nasab dengan ayah biologisnya. Secara langsung anak tersebut tidak memiliki wali nasab, karena wali nasab itu diambil dari keturunan ayah, Sehingga pihak pencatat nikah menolak untuk menikahkannya, disebabkan tidak memiliki wali mujbir. penulis tertarik untuk meneliti bagaimana penyelesaian pernikahan bagi wanita yang hanya bernasab kepada ibunya yang tidak memiliki nasab kepada ayah biologisnya dan faktor-faktor apa saja yang menyebabkan tercatat sebagai anak ibu. Penelitian ini dilaksanakan di Kecamatan Grujugan Kabupaten Bondowoso. Penelitian ini termasuk jenis penelitian lapangan (field research) dengan menggunakan metode kualitatif. Hasil dari penelitian ini: Pelaksanaan pernikahan anak yang bernasab pada ibunya saja, maka pernikahannya menggunakan wali hakim sebagai ganti dari wali nasabnya, dengan putusan dari Pengadilan Agama dalam menentukan wali hakim. Sedangkan penyebab tercatatnya sebagai anak ibu saja di Kecamatan Grujugan di sebabkan karena dua faktor yaitu, anak yang dihasilkan di luar pernikahan, dan ayah yang tidak diketahui keberadaannya. Kata Kunci: Pernikahan, Nasab, Grujugan Bondowoso